GIVEN OF ORGANIC MATTER TO THE POPULATION OF PHOSPHATE SOLUBILIZING MICROORGANISM IN ULTISOL SOIL - Nyang Vania Ayuningtyas Harini (Jurnal Peternakan (Jurnal of Animal Science), 2020)
One of the obstacles that causes the low agricultural production in Lampung is the type of Ultisol soil. Ultisol soil which is dominated by sand fraction that has experienced weathering. In general this soil has the potential to poison Al, Fe, and poor organic matter content. Adequate organic matter content and nutrient biology cycle are one of the keys to succescful soil managemen in the tropic soil. The use of ground cover plants, the addition of mulch compost or manure can improve soil productivity, supply nutrients to plants, support the rapid nutrient cycle through microbial biomass, and retain fertilizer applied. Organic matter is a decomposition of plant residues or soil microorganism that play an important role in soil fertility and is an important source of nutrient for plants. Organic matter can improve the physical, chemical, and biological properties of the soil. One of the biological properties of the soil is the presence of phosphate solubilizing microorganism. phosphate solubilizing microorganism is a microorganisms that plays an important role in dissolving P which are insoluble in soil. The ability of phosphate solubilizing microorganism varies greatly depending on the type of microbes, adaptability, to the ability to produce organic acids and enzymes. In the presence of organic matter, the activity and population of phosphate solubilizing microorganism will increase. phosphate solubilizing microorganism will use organic matter as an energy source to support increased activity and population in the soil.